Bioactive, antioxidant and antimicrobial properties of chemically fingerprinted essential oils extracted from Eucalyptus globulus: in-vitro and in-silico investigations - Nasir Shah, Said; Khan, Ibrar; Tul Muntaha, Sidra; Hayat, Azam; Ur Rehman, Mujaddad; Ali Shah, Tawaf; Siddique, Farhan; Salamatullah, Ahmad Mohammad; Mekonnen, Amare Bitew; Bourhia, Mohammed (Frontiers in Chemistry, 2023)
Innovative approaches are urgently required to treat divestating bacterial diseases in the face of rising bacterial resistance rates. The current investigative work focused on hydro-distilling Tasmanian blue gum (Eucalyptus globulus) to isolate the essential oil, which was then tested for bioactivity, antioxidant capacity, and antibacterial activity using in-vitro and in silico assays. The antioxidant activity was avualated against DPPH and FRAP. With results of 69.63 RSA (%) (µL/L AAE) at a concentration of 5 mL/L and 51.56 (µL/L AAE) at concentration of 90 ppm in the 2,20-diphenyl-1-picryl hydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays, respectively, the extracted oil indicated considerable antioxidant activity. The extracted oil demonstrated powerful antibacterial activity in in-vitro tests against both gram-positive and gram-negative bacterial strains, including Bordetella bronchiseptica (21mm), Staphylococcus epidermidis (19mm), and Staphylococcus aureus (19mm), with significant minimal inhibitory (MIC) and minimum bactericidal (MIB) concentrations.